Mortality from HIV/AIDS in adolescents and young adults: a temporal time series - Camila Moraes Garollo Piran; Beatriz Sousa da Fonseca; Natan Nascimento de Oliveira; Bianca Machado Cruz Shibukawa; Maria de Fátima Garcia Lopes Merino; Rosana Rosseto de Oliveira; Marcela Demitto Furtado (Rev Rene)
Objective: to analyze the trends of mortality from HIV/AIDS in adolescents and young adults. Methods: ecological, time series investigation of deaths by HIV/AIDS in adolescents and young adults, from 2009-2019 in Brazil, in populated areas included in records from the System of Information on Mortality. We applied correcting factors to the mortality rates and carried out analysis using polynomial regression modeling. Results: we analyzed 6,344 deaths by HIV/AIDS in adolescents and young adults. We found high mortality rates in young adults when compared to adolescents. There was a growing trend in the north of the country, in the age group from 10 to 14. Mortality rates were higher among males in all regions, with a reduction in the mean rate for white persons and an increase for black/brown persons. Conclusion: there was an increasing trend, followed by a decrease in the last few years, with relevant differences between regions. The age group from 20 to 24 and males presented the highest mean rates of deaths from this disease. Contributions to practice: most of all, our findings give support to health planning, considering the specificities of the public and the regions with the most growing trends, thus helping improve public policies.